Databank of 1977 Spanish Press - Språkbanken Text (University of Gothenburg, 2024)
This corpus contains texts from two different newspapers published in Spain,
namely "El País" and "Triunfo". The periodicals included are from 1977 and
include annotations for author, source, genre/section, as well as the
location of the article within its publication. It contains about 3,000
articles from periodicals by more than 400 different authors. This corpus
is part of SOL - Spanish Online.

Korpusen innehåller texter från tidningarna "El País" och "Triunfo", utgivna
i Spanien. De inkluderade utgåvorna är från 1977 och innehåller
annotationer för författare, källa, genre/kategori och platsen där artikeln
publicerades. Korpusen innehåller ca 3 000 tidningsartiklar skrivna av över
400 olika författare. Korpusen ingår i samlingen SOL - Spanska Online.
Banco de Datos de Prensa Española 1977
Keywords: Language Technology (Computational Linguistics); 1970s; newspapers; periodicals; Spain; Spanish; corpus; Natural Language Processing; Språkbehandling och datorlingvistik